Notions of Privacy at Early Modern European Courts. Reassessing the Public and Private Divide, 1400-1800. Edited by Dustin M. Neighbors, Lars Cyril Norgaard, and Elena Woodacre. Amsterdam: Amsterdam University Press, 2024. ISBN 978-94-6372-007-6. vii + 304 pp - Sanne Maekelberg (Royal Studies Journal)
Notions of Privacy at Early Modern European Courts. Reassessing the Public and Private Divide, 1400-1800. Edited by Dustin M. Neighbors, Lars Cyril Norgaard, and Elena Woodacre. Amsterdam: Amsterdam University Press, 2024. ISBN 978-94-6372-007-6. vii + 304 pp